2021
DOI: 10.37201/req/018.2021
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of remdesivir in hospitalized patients with COVID-19

Abstract: Objective. Controversial results on remdesivir efficacy have been reported. We aimed to report our real-life experience with the use of remdesivir from its availability in Spain. Methods. We performed a descriptive study of all patients admitted for ≥48 hours with confirmed COVID-19 who received remdesivir between the 1st of July and the 30th of September 2020. Results. A total of 123 patients out of 242 admitted with COVID-19 at our hospital (50.8%) received remdesivir. Median age was 58 years, 61% were males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
4
18
2
Order By: Relevance
“…Nevertheless, aspects such as the fact that the overall mortality, significant in the total study population of the ACTT-1 trial, reflects the huge COVID-19 heterogeneity in behavior in different patient subgroups and the difficulty of randomizing benefits coming from the highest sample size subgroup ( n = 232 in remdesivir group and n = 203 in placebo group) should be taken into account [ 10 ]. Furthermore, in a real-life cohort of patients with severe pneumonia receiving low-flow oxygen-therapy treated with remdesivir, the 30-day mortality rate observed was 4.1% [ 26 ], very similar to that reported in the ACTT-1 trial [ 10 ]. This suggests that the results observed in this study could be in line with reality.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, aspects such as the fact that the overall mortality, significant in the total study population of the ACTT-1 trial, reflects the huge COVID-19 heterogeneity in behavior in different patient subgroups and the difficulty of randomizing benefits coming from the highest sample size subgroup ( n = 232 in remdesivir group and n = 203 in placebo group) should be taken into account [ 10 ]. Furthermore, in a real-life cohort of patients with severe pneumonia receiving low-flow oxygen-therapy treated with remdesivir, the 30-day mortality rate observed was 4.1% [ 26 ], very similar to that reported in the ACTT-1 trial [ 10 ]. This suggests that the results observed in this study could be in line with reality.…”
Section: Discussionsupporting
confidence: 59%
“…Recent real-word studies reporting data on the use of remdesivir [17] also compared it with lopinavir/ritonavir [18]. Some important meta-analysis showed that COVID-19 patients receiving remdesivir showed significantly higher rates of recovery and hospital discharge with lower rates of serious adverse events when compared to patients receiving other treatments [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…After a median (IQR) 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days, clinical recovery was observed in 197 pts (89%), 159 of whom also reported virological recovery after a median (IQR) 20 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) days.…”
Section: General Characteristics Of Study Populationmentioning
confidence: 99%
“…Up until nowadays, limited data exist regarding the use of Remdesivir in real life [ 22 , 23 , 24 , 25 , 26 ]. Could Remdesivir represent a therapeutic option in the current epidemiological scenario, considering the scarcity of valid therapeutic alternatives available and the frequent, rapid evolution of SARS-CoV-2 pneumonia also in patients with mild COVID-19 and recent symptom onset?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation